IDENTIFYING THE INFLUENCES OF COMPASS LIMITED EDITION SERIES CHARACTERISTICS TOWARDS PURCHASE INTENTION - Indrayana, Gading
The rise of shoe brands in Indonesia indicates a growing industry. This has increased business competition, requiring new innovations and strategies. Shoe brands often use a limited quantity release, or limited-edition shoes (LES) as a marketing strategy because it creates a shortage of supply and demand, which makes consumers twice as likely to buy the product. OLE is a limited edition shoe released once, and RLE is a limited edition shoe released several times, but the release is adjusted to consumer desires and modernization of production. Because this method increases consumer desire to buy, Compass, an Indonesian shoe brand, used it to boost sales and consumer interest, and it was successful. Negative effects include disappointed and angry consumers who can't buy their products. So this study aims to analyze how Compass limited edition shoes affect customer purchase intentions by identifying profit value factors and brand trust. PLS-SEM was used to analyze the relationship between variables in an online survey of 205 buyers or owners of limited edition compass shoes on Java aged 18 to 40. The results show that in OLE, the limited edition implementation affects the customer's desire to buy the Compass limited edition shoe product. Emotional, social, and economic value affect brand trust positively. Emotional and economic value positively influenced consumers' purchase intentions, but social value didn't. Emotional, social, and economic RLE values boost brand trust and consumer buying intentions. The results suggest that for OLE and RLE shoes, Compass must maintain its unique character in each collection, increase collaboration, provide more detailed information about limited edition shoes, and limit the number of purchases by the same buyer. This helps OLE and RLE consumers feel the value of the shoes they buy, increasing their purchase intention. By doing this research, it is hoped that business actors and marketers will better understand how companies can increase purchase intention by releasing limited edition shoes for OLE and RLE.